2002
DOI: 10.1037/0096-1523.28.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness, forward and backward.

Abstract: In these experiments, 2 letters were presented sequentially to the left and right of fixation, followed by pattern masks. Report was cued by spatial location (Experiments 1a, 1b, 2, 4, and 5) or temporal position (Experiments 3, 4, and 5). In all experiments, 2 identical letters on a trial resulted in reduced accuracy of report (repetition blindness; RB) for both the 1st and 2nd presented letters. This decrement was greater for the 2nd letter if subjects expected temporal cues, but tended to be greater for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…) ness, provide effective visual cues to attract attention and enhance the perception of the targets. These data support a type-token (Chun, 1997;Kanwisher, 1987;Neill et al, 2002) account of visual processing and suggest that when establishing the presence of two temporally separated items in the environment, not only is it important how they differ featurally from one another, but also how they differ from other stimuli in close temporal proximity.…”
Section: Notessupporting
confidence: 63%
See 2 more Smart Citations
“…) ness, provide effective visual cues to attract attention and enhance the perception of the targets. These data support a type-token (Chun, 1997;Kanwisher, 1987;Neill et al, 2002) account of visual processing and suggest that when establishing the presence of two temporally separated items in the environment, not only is it important how they differ featurally from one another, but also how they differ from other stimuli in close temporal proximity.…”
Section: Notessupporting
confidence: 63%
“…Previous work has shown that categorical differences between targets and distractors do not remove repetition blindness; therefore, it appears that featural differences, rather than just general distinctivetractors enhance target registration in dual-target RSVP search; however, the data also have implications for models of repetition blindness. We have offered a type-token account of our data (Chun, 1997;Kanwisher, 1987;Neill et al, 2002;Potter, 1999); however, alternative theoretical accounts have been offered to explain the processing of repeated stimuli in RSVP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the fallibility of this discrimination that lies at the heart of repetition blindness. This notion is quite similar to a modified type-token account offered by Neill, Neely, Hutchison, Kahan, and VerWys (2002). That account was motivated by the finding that, depending on how list report was cued, repetition blindness could be greater for report of the first member of a repeated pair than for the second member.…”
Section: Repetition Blindness As Perception or Memory?mentioning
confidence: 76%
“…Rather, the critical process involved in discounting is one of misattribution, which fits readily into the evaluation component of the construction account. Thus, as with the Neill et al (2002) instantiation-contextualization account, processes that comprise the ROUSE model's explanation of repetition blindness are more naturally compatible with a construction than they are with a type-token account.…”
Section: Repetition Blindness As Perception or Memory?mentioning
confidence: 87%